Analysis of the Role of Podcasts as a New Platform in Multiplatform Journalism in the Digital Era - Amelia, Amelia; Ningsih, Widia (Islamic Journal of Communication and Public Discourse, 2024)
This study aims to analyze the role of podcasts as a new platform in multiplatform journalism, especially in presenting in-depth and critical information to audiences in Indonesia. This study uses a content analysis method on two podcast episodes: "Deliberation-in Political Dynasties, SYL Corruption, and Mass Organization Mining Permits" from the Narasi Conference podcast and "Land for Rice Field Printing Projects in the Land of Papua" from the podcast Bocor Alus Tempo. The results of the study show that journalistic podcasts are able to present in-depth and interactive discussions on social, political, and environmental issues that are not always comprehensively raised by mainstream media. The study concludes that podcasts have great potential as a more flexible and reflective journalism medium, but they face challenges related to regulation, content credibility, and sustainable business models. The suggestions provided include improving ethical and regulatory standards in podcast content production, empowering indigenous peoples in development projects, and exploring business models that support the sustainability of independent podcasts in Indonesia.